An Experimental Study of Effects of Media Implication on Self-Report Symptoms Related With MP Use - Gao, Peng; Zheng, Fei-Zhou; He, Min-Di; Li, Min; Deng, Ping; Zhou, Zhou; Yu, Zheng-Ping; Zhang, Lei (Frontiers in Public Health, 2020)
Along with gradually increases in mobile phone (MP) use, the mass media has played a vital role in informing the public regarding the potential health hazards of MP use. These media warnings have prompted public worries about health. The aim of the present study is to investigate the effects of media warnings about the possible health hazards of MP use on self-reported symptoms. Participants were 703 undergraduate students who volunteered to take part in an experimental study between August 2013 and July 2015. After completing baseline questionnaires containing information on demographics, MP usage and possible confounding variables, the participants were randomly clustered assigned to a video treatment group (watching a 5-min video about the possible health hazards of MP use) or a control group. Then, they completed another set of questionnaires containing 6 self-reported physical symptoms and the Beck Depression Inventory (BDI). Chi-squared tests, Mann-Whitney U-tests and logistic regression models were applied in the data analysis. Participants in the video group reported significantly more frequent headache (P = 0.01), fatigue (P = 0.00), memory loss (P = 0.03), inattention (P = 0.00), and higher level of depression (P = 0.05) than those in the control group. Additionally, the prevalence of memory loss (β = 0.071, P = 0.03) and inattention (β = 0.110, P = 0.00) were significantly higher in participants with higher level of depression who watched the video. Media warnings about the possible health hazards of MP use promote people to report physical symptoms and psychological problems. Considering this tendency, more moderate and scientific media information is needed to alleviate public worries about MP use.